2009
DOI: 10.1097/id.0b013e31818c6a50
|View full text |Cite
|
Sign up to set email alerts
|

Implant Placement Accuracy When Using Stereolithographic Template as a Surgical Guide: Preliminary Results

Abstract: When measured using the CMM, the stereolithographic surgical template was sufficiently accurate in transferring the planned implant position to the surgical field relative to the implant angulations and point of entrance. Further clinical studies using a greater number of patients are needed to confirm the results of this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…To the best knowledge of the authors, no studies were performed on the accuracy of virtually planned implant placement in the fully edentulous maxilla after an augmentation procedure. Also, in contrast to many other accuracy studies without augmentation procedure, the result of this study was interpreted in a clinically relevant manner by decomposing three‐dimensional results into the BL and MD directions.…”
Section: Discussionmentioning
confidence: 99%
“…To the best knowledge of the authors, no studies were performed on the accuracy of virtually planned implant placement in the fully edentulous maxilla after an augmentation procedure. Also, in contrast to many other accuracy studies without augmentation procedure, the result of this study was interpreted in a clinically relevant manner by decomposing three‐dimensional results into the BL and MD directions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, deviations between planned and postoperative implant position, implant deviations were determined in a clinically relevant manner, that is, decomposed in a BL and MD vector, and not solely in a three‐dimensional distance as performed in most other studies …”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed in vivo results on the accuracy of implant placement using surgical templates. However, most of these studies presented accuracy results consisting of a combination of fully edentulous and partially edentulous, different types of support of the surgical template and implant placement in both mandible and maxilla …”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of articles in the literature addressing the efficacy of the transference of images from the study of implant placement to the surgical field 29 . Di Giacomo et al 30 used six surgical guides in four patients with 21 implants inserted and observed differences in the distances between the planned and actual implant positions at the implant level of, in average, 1.45mm and 2.99mm, respectively.…”
Section: Discussionmentioning
confidence: 99%